Probiotics Ingestion Does Not Directly Affect Thyroid Hormonal Parameters in Hypothyroid Patients on Levothyroxine Treatment - Spaggiari, Giorgia; Brigante, Giulia; De Vincentis, Sara; Cattini, Umberto; Roli, Laura; De Santis, Maria Cristina; Baraldi, Enrica; Tagliavini, Simonetta; Varani, Manuela; Trenti, Tommaso; Rochira, Vincenzo; Simoni, Manuela; et al. (Frontiers in Endocrinology, 2017)
Purpose The relationship between probiotics and levothyroxine (LT4) requirement has not yet been investigated. The aim of this study was to assess whether a mixture of highly charged Lactobacilli and Bifidobacteria (VSL#3®) is able to influence LT4 metabolism acting on the gut microbiota. Methods A prospective, randomized, single-blind, controlled, investigator-started clinical trial was carried out. Patients with primary hypothyroidism were randomly assigned to the study (VSL#3® + LT4) and the control group (LT4). A 2-month treatment phase was followed by 2 months of follow-up. Clinical examination, blood tests for thyroid function and for peripheral tissue markers of thyroid hormones (PTM) were performed monthly. LT4 dose adjustments were performed when necessary. Results Thirty-nine patients were enrolled in the study group and 41 in the control group. No difference in thyroid function [thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), and free thyroxine (fT4)] and PTM was found between groups and among visits. FT3/fT4 ratio was directly correlated to TSH at each visit in both groups, with the exception of the first evaluation of probiotics-treated subjects (rho = 0.287, p = 0.076). LT4 daily dose adjustments occurred more frequently in the control than in the study group (p = 0.007), despite no differences in the mean LT4 daily dose. In particular, LT4 doses were increased six times in the control group and decreased four times in the study group. Conclusion VSL#3® does not directly alter thyroid functional compensation. A probiotics-mediated influence on thyroid hormones homeostasis is suggested since probiotics supplementation could be able to prevent serum hormonal fluctuations. ClinicalTrials.gov ID Registration number NCT03095963.